Food allergies : a complete guide for eating when your life depends on it - Sicherer, Scott H. (Baltimore : Johns Hopkins University Press, 2013)
Posing the questions that anyone with food allergies will think to ask, this book provides practical, emotional, and scientific guidance on the topics that affect your life. Allergy expert Scott H. Sicherer addresses the full spectrum of food allergies, from mild to life threatening, from single foods to food families, clearing up misconceptions along the way. He explains how exposure to foods can bring about an allergic response, describes the symptoms of food allergy, and illuminates how food allergies develop. He also recommends tests for diagnosing both food allergies and chronic health problems caused by food allergies, such as eczema, hives, and respiratory and gastrointestinal symptoms. Food Allergies thoroughly explains how to prevent exposure to a known allergen at home, at school, in restaurants, and elsewhere and what to do if exposure occurs, including how to handle an anaphylactic emergency. Dr. Sicherer also reviews food reactions that are not allergic (such as lactose intolerance), advises how to get adequate nutrition when you must avoid dietary staples, and discusses whether allergies ever go away.
1. What are the basic facts about food allergy? -- Allergy and other adverse reactions to food -- Symptoms and illnesses -- Severity -- When symptoms are not a food allergy -- Prevalence of food allergies -- Causes and triggers of food allergies -- Peanuts -- Eggs -- Cow's milk -- Wheat and other grains -- Tree nuts -- Seeds -- Soy -- Legumes -- Vegetables and starches -- Fruits -- Meats -- Fish -- Shellfish -- Spices -- Alcoholic beverages -- Miscellaneous food allergens and colors, additives, and preservatives -- When to seek help -- Latex and food allergies -- Unusual food reactions -- 2. What do I need to tell the doctor to help get a food allergy diagnosis? -- Alternative therapies -- Tests to avoid -- 3. These food allergy tests are confusing! What do they mean? -- Skin tests -- Blood tests -- Elimination diets -- Oral food challenges (feeding tests) -- Unproven and disproven tests -- Improved diagnostic tests and component testing -- Reasons for unexpected test results -- 4. What is anaphylaxis and how do I treat it? -- Epinephrine -- Antihistamines -- Written emergency plans, education, medical identification jewelry, management issues -- Predicting anaphylaxis -- Exercise and anaphylaxis -- Anaphylaxis treatment quiz -- 5. What chronic health problems are caused by food allergy? -- Chronic illnesses and food -- Respiratory symptoms -- Hives -- Atopic dermatitis (eczema) -- Gastrointestinal, digestive illnesses -- Colic, constipation, irritable bowel syndrome, and reflux -- Celiac disease (gluten-sensitive enteropathy) -- Proctocolitis (food protein-induced proctocolitis) -- Food protein-induced enterocolitis syndrome -- Food protein enteropathy and protein intolerance -- Eosinophilic esophagitis and other eosinophilic gut diseases -- Delayed allergic reactions -- Chronic illnesses unrelated to food allergies -- 6. How do I avoid allergic reactions to foods? -- Cross-contact -- Amounts that trigger reaction and casual exposure -- Avoidance at home -- Purchasing manufactured products -- Restaurants -- Social outings and family gatherings -- School -- Camp -- Work -- Travel -- Dating and relationships -- Special exposure risks -- Risks and risk reduction controversies -- The peanut-sniffing dog -- 7. How do I manage a food allergy while living a normal and healthy lifestyle, with adequate nutrition? -- Lifestyle and quality of life -- Emotional concerns and anxiety -- Interpersonal relationships and bullying -- Nutrition -- 8. Will these food allergies ever go away? -- Food allergy resolution -- Course of allergies to specific foods -- Course of illnesses caused by food allergies -- Recurrence of a food allergy and development of new food allergies -- The air-food connection -- 9. Is there any way to prevent food allergies? -- Pregnancy diets -- Breast feeding and formulas -- Introducing solid foods -- Nondietary aspects of prevention -- Difficulties in studying allergy prevention -- Insights on prevention form worldwide observations -- 10. Will there be a cure or better treatment of food allergy? -- Food allergy research -- Approaches to treat any type of food allergy -- Approaches to treat allergies to specific foods -- Treatments of specific food-allergic diseases -- Unproven treatments -- Participating food allergy research -- Chinese herbal therapies -- 11. How do I get more help and information to manage food allergies? -- Education resources -- Support groups, advocacy, and research -- Handy forms -- Selected medical references.
'A Johns Hopkins Press health book'
Includes bibliographical references (p. 270-271) and index.
Keywords: Food Hypersensitivity -- therapy